Solar Gas Turbine Systems with Centrifugal Particle Receivers, for Remote Power Generation. (May 2015) - Prosin, T.; Pryor, T.; Creagh, C.; Amsbeck, L.; Uhlig, R.
Abstract: There is a growing demand from remote communities in Australia to increase the amount of decentralised renewable energy in their energy supply mix in order to decrease their fuel costs. In contrast to large scale concentrated solar power (CSP) plants, small solar-hybrid gasturbine systems promise a way to decentralise electricity generation at power levels in the range of 0.1-10MWe, and reduce to cost of energy production for off-grid, isolated communities. Thermal storage provides such CSP systems with an advantage over photovoltaic (PV) technology as this would be potentially cheaper than adding batteries to PV systems or providing stand-by back-up systems such as diesel fuelled generators. Hybrid operation withconventional fuels and solar thermal collection and storage ensures the availability of power even if short term solar radiation is not sufficient or the thermal storage is empty. This paper presents initial modellingresults of a centrifugal receiver (CentRec)system, using hourly weather data of regional Australia for a 100 kWe microturbine as well as a more efficient and cost effective 4.6MWe unit. The simulations involve calculation and optimisation of the heliostat field, by calculating heliostat by heliostat annual performance. This is combinedwith a model of the receiver efficiency based on experimental figures and a model of the particle storage system and turbine performance data. The optimized design for 15 hours of thermal storage capacity results in a tower height of 35m and a solar field size of 2100m 2 for the 100 kWe turbine, and a tower height of 115m and solar field size of 50 000m 2 for the 4.6MWe turbine. The solar field provides a greater portion of the operational energy requirement for the 100kWe turbine, as the TIT of the 4.6MWe turbine (1150 °C) is greater than what the solar system can provide. System evaluations of the two particle receiver systems, with a selection of cost assumptions, are then compared to the current conventional means of supplying energy in such remote locations.